Evaluation of the effectiveness of green tea mouth rinse on oral halitosis, tongue coating, and plaque accumulation in comparison with 0.2% chlorhexidine mouth rinse - A double-blind randomized control trial - Pratibha Sharma; Byalakere Rudraiah Chandrashekar; Kenganura Mruthunjaya; Vivek Bhaskar (Wolters Kluwer Medknow Publications, 2023)
Background: Green tea (Camellia sinensis) mouth rinse is found effective in reducing periodontitis. However, studies evaluating the effectiveness of green tea extracts in reducing oral halitosis and tongue coating on Indian population were scanty. Objective: The objective of this study was to evaluate the effectiveness of green tea-based mouth rinse in comparison with 0.2% chlorhexidine gluconate mouth rinse in reducing dental plaque, tongue coating, and halitosis among human volunteers. Materials and Methods: This was a parallel-arm double-blind randomized controlled trial conducted in two residential hostels in Mysuru city over 21 days. 90 adult participants were recruited and randomized into three groups: Group A: mouth rinse containing saline, Group B: 5% C. sinensis mouth rinse, and Group C: 0.2% chlorhexidine diluted to with equal quantity of water. Preintervention prophylaxis was done; tongue coating and oral halitosis scores were recorded and compared between the groups at baseline and after 21 days. Results: The mean plaque buildup at postintervention was highest in Group 1 (2.45 ± 0.38) followed by Group 3 (1.18 ± 0.12) and Group 2 (1.08 ± 0.11) in the descending order. The mean oral halitosis score was highest in Group 1 (3.00 ± 0.79) followed by Group 3 (1.53 ± 0.50) and Group 2 (1.50 ± 0.50) in the descending order. The mean tongue coating score was highest in Group 1 (1.17 ± 0.47) followed by Group 2 (0.75 ± 0.36) and Group 3 (0.69 ± 0.34) in the descending order. Conclusion: Five percent C. sinensis mouth rinse is as effective as commercially available 0.2% chlorhexidine mouthwash in reducing plaque deposition, tongue coating, and oral halitosis.